PENGARUH STRATEGI PEMBELAJARAN DAN GAYA KOGNITIF TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN SEJARAH - SULANI, PUJI (Program Studi Pendidikan Sejarah Pascasarjana Universitas Negeri Jakarta, 2014)
This research was to determine the effect of learning strategies and cognitive style toward studentâs critical thinking skill in learning history. This research concludes that studentâs critical thinking skills in learning history: (1) had taught using PBL strategies are higher than those taught using conventional learning strategies; (2)who occupied by FI cognitive style higher than those who occupied by FD cognitive style; (3) there are significant interaction between the strategies of learning and cognitive styles on studentâs critical thinking skill in learning history; (4) who are taught using PBL strategies and occupied by FI cognitive style is higher than those taught using conventional learning strategies and occupied by FI cognitive style; (5) who are taught using PBL strategies and occupied by FD cognitive style is lower than those taught using the conventional learning strategies and occupied by FD cognitive style; (6) who are taught using PBL strategies and occupied by FI cognitive style is higher than those taught using PBL strategies and occupied by FD cognitive style; and (7) who are taught using conventional learning strategies and occupied by FI with cognitive style is lower than those taught using conventional learning strategies and occupied by FD cognitive style.Keywords: learning strategies, cognitive styles, critical thinking skills.